2015
DOI: 10.1556/0806.43.2015.017
|View full text |Cite
|
Sign up to set email alerts
|

Correlation betweenFusarium graminearumand deoxynivalenol during the 2012/13 wheat Fusarium head blight outbreak in Argentina

Abstract: Fusarium graminearum (Schwabe) is reported as the main causal agent of Fusarium head blight in Argentina. The disease causes great losses in humid and semi-humid regions of the world, reducing grain yield and quality. During 2012/13 harvest season, a severe epidemic occurred in Argentina. The aims of this work were to determine the F. graminearum incidence and deoxynivalenol accumulation in wheat grain and flour samples obtained from two of the main wheat growing regions from Argentina. Levels of the pathogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…With stronger FHB infections, these results might have been different. Between DON content and FHB incidence positive correlation appeared, which was also confirmed in studies of Blandino et al (2006) and Palazzini et al (2015).…”
Section: Cereal Research Communications 46 2018supporting
confidence: 75%
“…With stronger FHB infections, these results might have been different. Between DON content and FHB incidence positive correlation appeared, which was also confirmed in studies of Blandino et al (2006) and Palazzini et al (2015).…”
Section: Cereal Research Communications 46 2018supporting
confidence: 75%
“…Fusarium head blight is caused by species within the F. graminearum complex. In Argentina, F. graminearum sensu stricto is the main pathogen associated with the disease [ 1 , 16 ]. In the pathosystem wheat– F. graminearum , it was demonstrated that both SA and JA signaling are associated with FHB resistance [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the last 60 years, several epidemics of FHB of varying degrees of severity have occurred in Argentina. During 2012, a severe FHB outbreak occurred in the main wheat growing area, with estimated losses of up to 70% [ 1 ]. The concern of this disease is due to the reduction in grain yield and quality and the potential for contamination with mycotoxins, mainly trichothecenes such as deoxynivalenol (DON) and its acetylated derivatives 3-acetyl-deoxynivalenol (3-ADON) and 15-acetyl-deoxynivalenol (15-ADON) and deoxynivalenol 3 β– d -glucoside (DON-3-G) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, yield losses as a result of FHB were estimated to be US$ 3 billion between the early 1990s and 2008 . Severe FHB outbreaks also frequently occurred in the main wheat growing area in Europe, South America and Latin America . The FHB epidemic has increased in China since 2010 and occurs in about 20% of the planting area of wheat .…”
Section: Introductionmentioning
confidence: 99%
“…2 Severe FHB outbreaks also frequently occurred in the main wheat growing area in Europe, South America and Latin America. 3,4 The FHB epidemic has increased in China since 2010 and occurs in about 20% of the planting area of wheat. 5 Currently, chemical fungicide control is the most effective strategy for controlling FHB due to the unavailability of FHB resistant wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%